Context and prospects for decentralized composting of Municipal Solid Waste in Brazil - Castro, Marco Aurélio Soares de; Lafratta, Jacqueline Mazini; Moura, Pedro Silva Daltro (Revista Nacional de Gerenciamento de Cidades, 2023)
Factors such as urbanization contribute to the constant increase in the generation of municipal solid waste, of which the organic fraction is the most significant. Composting is a versatile and scalable alternative for managing organic waste, and European countries have been intensifying the adoption of this strategy, both centrally and decentrally. On the other hand, the management of the Organic Fraction of Municipal Solid Waste (OFMSW) in Brazil, with the exception of unsuccessful experiments with centralized composting systems, is limited to disposal in landfills or dumps, rendering recoverable organic material useless and generating significant emissions of methane, one of the main greenhouse gases. Studies addressing decentralized composting as a strategy to improve waste management are still infrequent in Brazil. In this context, this article aimed to outline an overview of the generation of OFMSW in the world and in Brazil, as well as initiatives for its proper management. Based on a literature review, it compares the management of OFMSW in Europe and Brazil, and points out perspectives from the current Brazilian regulatory framework. Then, it discusses the potential benefits and challenges in implementing and operating decentralized systems. Decentralized composting (community or domestic) is a low-cost alternative for the management of OFMSW, but requires citizen engagement, in addition to attention to the quality of the final products. Future studies should address the positive impacts and possible restrictions of this alternative in Brazilian contexts, contributing to enable its integration into the management models currently adopted in the country.